2017
DOI: 10.5751/es-08956-220116
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling biodiversity conservation and agricultural expansion in the subarctic environment of Iceland

Abstract: ABSTRACT. Intensified agricultural practices have driven biodiversity loss throughout the world, and although many actions aimed at halting and reversing these declines have been developed, their effectiveness depends greatly on the willingness of stakeholders to take part in conservation management. Knowledge of the willingness and capacity of landowners to engage with conservation can therefore be key to designing successful management strategies in agricultural land. In Iceland, agriculture is currently at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…From our data, it is difficult to pinpoint major factors affecting waders (that had 36.4% of citations mentioning decline), as both climatic and natural drivers had an influence on them (through wetlands mechanisms that impact on resources). This could be because waders are a very diverse group that have a significant proportion of their members surviving some pressures in the environment through migrations (Kilpatrick et al, 2006) and probably contains some of the smallest waterbirds that people in most cases would not have specific knowledge on (J ohannesd ottir, Alves, Gill, & Gunnarsson, 2017).…”
Section: Rainfall and Surface Water Trendsmentioning
confidence: 99%
“…From our data, it is difficult to pinpoint major factors affecting waders (that had 36.4% of citations mentioning decline), as both climatic and natural drivers had an influence on them (through wetlands mechanisms that impact on resources). This could be because waders are a very diverse group that have a significant proportion of their members surviving some pressures in the environment through migrations (Kilpatrick et al, 2006) and probably contains some of the smallest waterbirds that people in most cases would not have specific knowledge on (J ohannesd ottir, Alves, Gill, & Gunnarsson, 2017).…”
Section: Rainfall and Surface Water Trendsmentioning
confidence: 99%
“…Agricultural expansion in Iceland is ongoing and, in a recent questionnaire study, the majority of Icelandic farmers surveyed reported that they are likely to expand their agricultural land within the next five years (Jóhannesdóttir et al 2017). To what extent that proposed expansion will be carried out remains uncertain, but Icelandic farmers own the majority of land below 400 m a.s.l.…”
Section: Agriculturementioning
confidence: 99%
“…National legislation is not well developed to deal with the cumulative impacts of the current rapid changes in land use on biodiversity, or with selective habitat protection at the scale of individual farms. Nevertheless, a recent study shows that farmers consider it important to have diverse birdlife on their land, and many report that they would be willing to participate in land management actions aimed at protecting and conserving birdlife (Jóhannesdóttir et al 2017). One management action that is currently available to farmers is funding to restore wetlands, but its implementation has been slow (7 km 2 have been restored in the last two decades), although farmers have been increasingly interested in restoration options (Barkarson et al 2016).…”
Section: Conservation Measures and Their Effectivenessmentioning
confidence: 99%
“…Each farm was surveyed twice: early, from midMay till mid-June, encompassing most egg-laying and incubation (peak nest initiation for the main species concerned is late May); and late, from mid-June to mid-July, the period that primarily encompasses chick rearing (Gunnarsson, 2010). At each location, all birds were counted along one line transect per management level (Bibby et al, 2000;J ohannesd ottir et al, 2014). As size and shape of agricultural fields can vary substantially, transect length and width were limited by field size (each transect was located within a single field) but the single observer (LJ) aimed to keep the surveyed area similar to ensure constant survey effort (average transect length (AE SD) = 253 AE 75 m; width = 92 AE 24 m, corresponding to an average survey area (AE SD) of 2.3 AE 0.8 ha).…”
Section: Bird Surveysmentioning
confidence: 99%